2022
DOI: 10.1093/mnrasl/slac136
|View full text |Cite
|
Sign up to set email alerts
|

A first look at the SMACS0723 JWST ERO: spectroscopic redshifts, stellar masses, and star-formation histories

Abstract: We present a first-look analysis of the JWST ERO data in the SMACS J0723.3-7327 cluster field. We begin by reporting 10 new spectroscopic redshifts from λobs = 1.8 − 5.2μm NIRSpec medium-resolution (R = λ/Δλ = 1000) data. These are determined via multiple high-SNR emission line detections, with 5 objects at 1 < z < 3 displaying multiple rest-frame near-infrared Hydrogen Paschen lines, and 5 objects at 5 < z < 9 displaying rest-frame optical Oxygen and Hydrogen Balmer lines. For the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
76
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 37 publications
8
76
0
Order By: Relevance
“…However the much higher signal-to-noise ratio detection from the MIPS imaging suggests that the northern spiral galaxy is the counterpart. In addition, one recent JWST study has suggested that the southern compact source to be a z ∼ 4.5 quiescent galaxy (Carnall et al 2022). We therefore identify the northern spiral galaxy to be the JWST counterpart for 850.025.…”
Section: Samplementioning
confidence: 81%
“…However the much higher signal-to-noise ratio detection from the MIPS imaging suggests that the northern spiral galaxy is the counterpart. In addition, one recent JWST study has suggested that the southern compact source to be a z ∼ 4.5 quiescent galaxy (Carnall et al 2022). We therefore identify the northern spiral galaxy to be the JWST counterpart for 850.025.…”
Section: Samplementioning
confidence: 81%
“…The directly measured circularized half-light radii (i.e., corrected for the galaxy ellipticity) range from 0.28 to 0.42 kpc (see Table 3). If we apply a rough correction for lensing amplification due to the foreground galaxy cluster, using the reported magnification values from Carnall et al (2023) that were obtained from the lens model provided by the RELICS team (Coe et al 2019), the sizes drop to 0.1-0.26 kpc. These lensing corrections are modest for two of the sources, with the exception being a magnification ∼10 and a corresponding reduction in circularized radius of ∼1/3× for J072326-732656 (04590) (04590).…”
Section: Size and Surface Brightness Comparisonsmentioning
confidence: 99%
“…a Gravitational lensing magnifications are taken fromCarnall et al (2023). b Lensing corrected sizes are approximated as (observed radius)/ magnification .…”
mentioning
confidence: 99%
“…The infrared photometric properties of galaxies at z ∼ 1-2 are studied with the NIRCam and MIRI images of the ERO SMACS J0723 observations in conjunction with the ALMA archival data (Cheng et al 2022). The ERO NIRSpec observations in SMACS J0723 provide high-quality spectra that allow us to identify 10 galaxies at z = 1.2-8.5, 3 of which reside at z = 7.7-8.5 (Carnall et al 2023), and to characterize the interstellar medium of the galaxies (Schaerer et al 2022;Curti et al 2023). NIRISS spectroscopic data complements the NIRSpec observations and provide a spectroscopic sample of z ∼ 1-8 galaxies (Boyett et al 2022;Roberts-Borsani et al 2022;Wang et al 2022;Marchesini et al 2023).…”
Section: Introductionmentioning
confidence: 99%